Pentingnya Komunikasi dan Pendampingan Pastoral bagi Penghayatan Sakramen Perkawinan Keluarga Katolik sebagai Ecclesia Domestica di Tengah Tantangan Zaman dalam Terang Kanon 1134 - Damian Deveuster Darvis Tarung; Yohanes Subani; Siprianus Soleman Senda (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The Catholic family as Ecclesia Domestica faces challenges in bridging the gap between the theological ideal of Canon 1134 and pastoral reality. This qualitative research employs library research with a reflective theological-pastoral approach to analyze magisterial documents and pastoral studies through theological-contextual hermeneutics. The study aims to examine the lived experience of the sacrament of marriage in light of Canon 1134 and explore effective pastoral strategies. Findings reveal systemic root problems in the form of defectus consensus, evidenced by 65.19% of nullity cases in the Manado Diocese stemming from error qualificatus, which originates from psychological immaturity, economic pressures, and inadequate pre-marriage formation. Nevertheless, grassroots communities prove effective in strengthening family resilience. As a solution, the study recommends a practical accompaniment model based on "Family Cells" with concrete discussion guides and integrated pre-marriage formation encompassing conflict simulation and tiered counseling. The transformation of pastoral approach from doctrinal to practical through accompaniment communities is essential so that the sacramental bond can be lived as a dynamic grace that strengthens families to become witnesses of Christ's love